Appraising Effective Utilization of Instructional Materials for Teaching and Learning of Agricultural Science in Senior Secondary Schools in Gombe State, Nigeria - Manzo Crew Dennis; Egunsola, A. O. E; Sarki, R.A (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
The purpose of this study was to appraise the effective utilization of instructional materials for teaching and learning of Agricultural Science in senior secondary schools in Gombe State, Nigeria. The study which was descriptive survey research was conducted in Gombe State and was guided by three research questions and three null hypotheses. The population of the study was 406 respondents involving 184 agricultural science teachers and 222 school administrators from the 74 senior secondary schools in Gombe State. The sample size of the study was 196 respondents determined using Krejcie and Morgan (1970) sample size table. A structured questionnaire was used for data collection. 0.84 reliability index was obtained from the trial test of QEUIMTLASSSS using Cronbach Alpha. Data collected for the study was analyzed using Mean statistics and t-test. Findings of the study revealed among others that Out of the 26 items listed, only 16 items namely: school farm, watering cans, plant lifters, planting hoes, etc. were functional for teaching and learning of Agricultural Science in secondary schools in Gombe State; while Instructional materials such as school farm, watering cans, plant lifters, and shovels were highly utilized for teaching and learning of Agricultural Science in Secondary Schools in Gombe State. It was recommended, Secondary Schools' administrators in Gombe State should reward teachers who form good habit of maintaining available instructional materials in the school; Ministry of Education in Gombe State should increase supervision of lessons and review teachers' workload in order for teacher to be able to examine their students' academic progress and performance as the use of instructional materials have significant effect on the students' academic performance.